The rise of AI-powered companies - Candelon, François; Reeves, Martin (Inspiring the next game (Series), 2022)
"Artificial intelligence is emerging as a game-changer in the business world, with impacts across all sectors. AI allows business to process massive amounts of data instantaneously, and to scale solutions at almost zero marginal cost, forcing companies to adapt and reimagine their business and operations. The Rise of AI-Powered Companies examines some of the most successful examples of companies using artificial intelligence to their advantage. From AI-enabled countries across the globe that stayed resilient and strong in the face of COVID-19, to Business-to-Consumer businesses that transformed their product development processes thanks to unprecedented amounts of consumer data, increasing their revenues manifold along the way. The book then delves into the critical enablers to becoming AI-powered and the critical steps to activate and integrate them within business organizations. Starting with data strategy, it examines new forms of data sharing and how companies should think about governance and privacy risks. It then focuses on human-AI collaboration and its role in building a stronger team culture. Finally, "Responsible AI" is discussed as well as the impact of AI-powered businesses on society at large. AI-powered companies will become the norm in the years to come. By unpacking and showcasing the major steps of a successful AI transformation, this book will help guide organizations in making the critical leap to become AI-powered--essential to survive and remain competitive in the near future."--